2016
DOI: 10.1074/mcp.m115.056770
|View full text |Cite
|
Sign up to set email alerts
|

Ataxin-2 (Atxn2)-Knock-Out Mice Show Branched Chain Amino Acids and Fatty Acids Pathway Alterations

Abstract: Human Ataxin-2 (ATXN2) gene locus variants have been associated with obesity, diabetes mellitus type 1, and hypertension in genome-wide association studies, whereas mouse studies showed the knock-out of Atxn2 to lead to obesity, insulin resistance, and dyslipidemia. Intriguingly, the deficiency of ATXN2 protein orthologs in yeast and flies rescues the neurodegeneration process triggered by TDP-43 and Ataxin-1 toxicity. To understand the molecular effects of ATXN2 deficiency by unbiased approaches, we quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 79 publications
3
63
0
1
Order By: Relevance
“…Several lines of evidence implicate ataxin-2 in growth receptor regulation and RNA metabolism [25-28]. Recent expression profiling efforts in Atxn2 -knockoout mouse tissues demonstrated a selective downregulation of mitochondrial matrix components global proteome profiles and a preferential downregulation of calcium homeostasis factors together with an upregulation of mRNA translation factors in global transcriptomics [29-31]. The structure of ataxin-2 contains a PAM2 motif which mediates association with the poly(A)-binding protein PABP [12, 13, 32], thought to promote ataxin-2 association with polyribosomes [33].…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence implicate ataxin-2 in growth receptor regulation and RNA metabolism [25-28]. Recent expression profiling efforts in Atxn2 -knockoout mouse tissues demonstrated a selective downregulation of mitochondrial matrix components global proteome profiles and a preferential downregulation of calcium homeostasis factors together with an upregulation of mRNA translation factors in global transcriptomics [29-31]. The structure of ataxin-2 contains a PAM2 motif which mediates association with the poly(A)-binding protein PABP [12, 13, 32], thought to promote ataxin-2 association with polyribosomes [33].…”
Section: Introductionmentioning
confidence: 99%
“…Mice lacking Atxn2 are viable but show adult-onset obesity and reduced insulin receptor expression (17,18). A recent study shows that Atxn2 modulates nutrition and metabolism by regulating the pathways for the metabolism of branched-chain and other amino acids, metabolism of fatty acids, and the citric acid cycle (19). Finally, the human locus containing SH2B3 and ATXN2 is associated with type 1 diabetes (20).…”
mentioning
confidence: 99%
“…A recently published study documented that ATXN2 regulates numerous nutrient enzymes in the mitochondrial matrix as well as key factors that may respond to altered Ca 2 + storage in mitochondria, ATXN2 mutations lead to a profound mitochondrial dysfunction [45]. Mouse studies showed the knock-out of ATXN2 to lead to obesity, insulin resistance, and dyslipidemia [46]. …”
Section: Discussionmentioning
confidence: 99%